1989
DOI: 10.1128/jcm.27.7.1588-1593.1989
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delay in processing on lysis-centrifugation blood culture results from marrow transplant patients

Abstract: The effect of delay in processing on results of lysis-centrifugation (LC; Isolator) blood cultures was assessed in 4,577 paired blood specimens. Blood specimens were obtained at all hours from 384 febrile marrow transplant patients with indwelling venous catheters and were processed by the LC technique and by a conventional two-bottle method. Most patients (84%) were receiving broad-spectrum antibiotics at the time of blood culture. Specimens were delivered to the laboratory, where Isolator tubes were held at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Blood culture processing. All blood culture sets were processed for purposes of patient care, but only those cultures received with at least two of the three bottles or tubes adequately filled and within 8 h of collection (10,27) were included in the study. HBV-FM and BP26 bottles were processed on BACTEC 660 blood culture instruments.…”
Section: Methodsmentioning
confidence: 99%
“…Blood culture processing. All blood culture sets were processed for purposes of patient care, but only those cultures received with at least two of the three bottles or tubes adequately filled and within 8 h of collection (10,27) were included in the study. HBV-FM and BP26 bottles were processed on BACTEC 660 blood culture instruments.…”
Section: Methodsmentioning
confidence: 99%
“…The Isolator 10 tubes contain the following reagents in 0.7 mL of aqueous solution: saponin (cell‐lysing agent), propylene glycol (blocks the foaming tendency of saponin), and SPS (anticoagulant). At least 6 mL of blood should be inoculated into these tubes, which must be processed as soon as possible, or at most 8 h after the inoculation of blood [61].…”
Section: Manual Systemsmentioning
confidence: 99%
“…Previous studies on the delayed processing of Isolator tubes either have not examined mycobacteria specifically or have used a design different from that of the present study. The studies of Hamilton et al (6) and Cashman et al (2) showed that rapidly growing bacteria were viable in the Isolator system after hold times of 8 to 24 h but that delayed processing led to an increase in the time needed to recover certain species (e.g., streptococci and members of the family Enterobacteriaceae) and decreased quantitative recovery rates for certain species (Streptococcus pneumoniae, Haemophilus influenzae). Only one mycobacterial strain (identified only as atypical mycobacterium) was studied.…”
Section: Discussionmentioning
confidence: 99%
“…when Isolator tubes are held for more than 8 h before processing (2,6). In one clinical study, delays of >9 h in processing Isolator tubes was associated with a fivefold reduction in the number of cultures positive for MAC (14).…”
mentioning
confidence: 99%